Social Participation for Tourist Use: The Case of Parque Nacional Islas Marietas, Mexico (Revista LIDER, 2019)
The public use of natural protected areas include tourist, educational, interpretive, recreational and research uses performed by visitors who participate in nonextractive activities nor introduce strange elements in the area. The objective of this research was to establish the desired social and biophysical conditions for Parque Nacional Islas Marietas, Mexico. The research was carried out through participatory workshops using World–Café tool to promote dialogue among some 200 participants. The problem of visitation and recreational activities were discussed. They established concerns and opportunities, and then issued their conclusions regarding the problems that were ranked according to their importance, which were agreed upon by all. The problems that were identified and hierarchicly organized with respect to the visitation of the park through social participation were the following: concentration of visitors in the same place that exceeds the carrying capacity and reduces the quality of the experience; although tourism service providers have improved their attitude, there are still bad practices and violations of the rules; the promotion of the natural area is inadequate; surveillance is insufficient; the areas frequently visited have diminished their appeal for scuba diving and coral communities have been deteriorated. On this basis, the baseline for managing the area was socially established, a process that constitutes the basis for public use that is still in process, where different actors participate.